2020
DOI: 10.1002/jcph.1619
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Study Design Using Continuous Intravenous and Intraduodenal Infusions of Midazolam and Voriconazole for Mechanistic Quantitative Assessment of Hepatic and Intestinal CYP3A Inhibition

Abstract: The extent of a drug‐drug interaction (DDI) mediated by cytochrome P450 (CYP) 3A inhibitors is highly variable during a dosing interval, as it depends on the temporal course of victim and perpetrator drug concentrations at intestinal and hepatic CYP3A expression sites. Capturing the time course of inhibition is therefore difficult using standard DDI studies assessing changes in area under the curve; thus, a novel design was developed. In a 4‐period changeover pilot study, 6 healthy men received intraduodenal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…MDZ was used as a sensitive index substrate for CYP3A4, which metabolizes MDZ to 1‐hydroxy MDZ (60%–80%) and much lesser extent to 4‐hydroxy MDZ (5%). 4 , 17 When MDZ and JBPOS0101 were co‐administered after multiple doses of JBPOS0101, the decrease for C max of MDZ was not clinically significant because of its IV administration and bypassing the first‐pass intestinal CYP3A4 metabolism. 18 , 19 However, the AUC of MDZ was reduced by 30% compared to that when MDZ was administered alone, and it was attributed to the induction of hepatic CYP3A4 by JBPOS0101.…”
Section: Discussionmentioning
confidence: 99%
“…MDZ was used as a sensitive index substrate for CYP3A4, which metabolizes MDZ to 1‐hydroxy MDZ (60%–80%) and much lesser extent to 4‐hydroxy MDZ (5%). 4 , 17 When MDZ and JBPOS0101 were co‐administered after multiple doses of JBPOS0101, the decrease for C max of MDZ was not clinically significant because of its IV administration and bypassing the first‐pass intestinal CYP3A4 metabolism. 18 , 19 However, the AUC of MDZ was reduced by 30% compared to that when MDZ was administered alone, and it was attributed to the induction of hepatic CYP3A4 by JBPOS0101.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MDZ is a short-acting benzodiazepine used therapeutically for anesthesia induction and as a sedative [33]. In humans, 1 0 -OH-MDZ and 4-OH-MDZ constitute approximately 60% to 80% and 5%, respectively, of the systemic (i.e., primarily liver) biotransformation products of MDZ [34]. In the current study, we showed that CYP3A activity, as demonstrated by MDZ hydroxylation, is present in both rat brain MT and MC (Figure 4).…”
Section: Discussionmentioning
confidence: 99%